ANALISIS UNSUR INSTRINSIK DAN SOSIOLOGI SASTRA CERPEN MAYAH SANGI KARYA I MADE ASTIKA - Wiranti, Comank Ari; Dwipayoga, I Kadek Agus; Kartika Dewi, Ni Kadek; Kencana Dewi, I Gusti Ayu; Susanthi Pradnya Paramitha, Ni Made Ayu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Literature is a social reflection of society by authors through literary works. With that, the problems that exist in society are expressed by the author through literary works as a medium of criticism. One of the literary works is a short story or short story that contains a depiction of life expressed in written form. In the short story Mayah Sangi by I Made Astika is full of aspects of life. This study aims to find out how the intrinsic elements and aspects contained therein. The research method used is a qualitative research method using a literary sociology approach. The results of the research conducted by the author show a relationship between the intrinsic in the short story with aspects of literary sociology that are indirectly contained in the short story Mayah Sangi.